Flavobacterium chryseum sp. nov. and Flavobacterium psychroterrae sp. nov., novel environmental bacteria isolated from Antarctica - Králová, Stanislava; Švec, Pavel; Busse, Hans-Jürgen; Staňková, Eva; Váczi, Peter; Sedláček, Ivo (International journal of systematic and evolutionary microbiology, 2018)
A group of rod-shaped, aerobic, Gram-stain-negative, gliding bacteria producing flexirubin-type pigment was isolated from environmental samples collected in Antarctica in 2009-2014. Phylogenetic analysis of the almost complete 16S rRNA gene sequences revealed two separated branches belonging to the genus Flavobacterium. Group I (n=8), represented by strain CCM 8826T, shared the highest sequence similarity to Flavobacterium collinsii 983-08T (98.8 %) and Flavobacterium saccharophilum DSM 1811T (98.4 %), and group II (n=4) represented by strain CCM 8827T shared the highest similarity to Flavobacterium aquidurense WB 1.1-56T (99.6 %). High genetic homogeneity of both groups, separation from each other and from phylogenetically close Flavobacterium species was verified by the rep-PCR fingerprinting method. DNA-DNA hybridization confirmed low genomic relatedness between strain CCM 8826T and F. collinsii 983-08T and F. saccharophilum DSM 1811T (18 and 28 %, respectively) and between strain CCM 8827T and F. aquidurense WB 1.1-56T (27 %). Chemotaxonomic analyses of strains CCM 8826T and CCM 8827T revealed the respiratory quinone to be MK-6, the major identified polar lipid was phosphatidylethanolamine and the predominant polyamine was sym-homospermidine. The common major fatty acids were C15 : 0 iso, C17 : 0 iso 3OH, C15 : 1 iso G, Summed Feature 3 (C16 : 1ω7c/C16 : 1ω6c), C15 : 0 iso 3OH and additionally, C15 : 0 anteiso among group II members. All analyses confirmed that strains of group I and II represent two novel species of the genus Flavobacterium, for which the names Flavobacterium chryseum sp. nov. (type strain CCM 8826T=P3160T=LMG 30615T) and Flavobacterium psychroterrae sp. nov. (type strain CCM 8827T=P3922T=LMG 30616T) are proposed.
Keywords: mastné kyseliny; Spermidine; taxonomy; Antarctica; Fatty Acids; DNA bakterií; RNA, Ribosomal, 16S; DNA, Bacterial; hybridizace nukleových kyselin; pigmentace; Flavobacterium chryseum sp. nov.; Vitamin K 2; zastoupení bazí; půdní mikrobiologie; vitamin K 2; Pigmentation; Phylogeny; Antarktida; fosfatidylethanolaminy; Antarctic Regions; Base Composition; Bacterial Typing Techniques; Soil Microbiology; Flavobacterium psychroterrae sp.nov.; Sequence Analysis, DNA; Nucleic Acid Hybridization; phylogeny; techniky typizace bakterií; Phosphatidylethanolamines; sekvenční analýza DNA; Flavobacterium; fylogeneze; spermidin; RNA ribozomální 16S